Labour Market Outcomes of Second Generation Immigrants: How Heterogeneous Are They Really? - Stefanie Schurer (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
The second and third generation of immigrants have been the centre of a lively debate about the economic integration of immigrants into their host societies, but there is little empirical evidence on the German case. In this study I comprehensively portray the labour market outcomes of second generation immigrants in Germany. Special attention is attributed to observable heterogeneity in terms of country of origin and unobservable heterogeneity in terms of parental human capital, neighbourhood effects, and mixed marriage background. Pooled, static and dynamic panel data models, and a decomposition analysis are used to estimate and explain the average differences in hourly wages and unemployment probabilities separately for men and women. The results suggest that the second generation cannot be considered as one homogeneous group: some groups perform better, equally or worse than comparable German natives. Also, relative outcomes in wages depend mainly on observable characteristics, whereas relative unemployment risks are mainly driven by unobservable factors.
Keywords: C23; J15; J61; J62; 330; Panel data; second generation immigrants; labour market outcomes; random effects; dynamic models; decomposition analysis; Migranten; Ethnische Gruppe; Soziale Integration; Berufliche Integration; Schätzung; Deutschland